Ferromagnetic exchange, spin–orbit coupling and spiral magnetism at the LaAlO3/SrTiO3 interface - Banerjee, Sumilan; Erten, Onur; Randeria, Mohit (Nature physics, 2013)
The interface between two non-magnetic band insulators, LaAlO 3 and SrTiO 3 , can exhibit conductivity, superconductivity and magnetism. These interfacial phenomena can be reconciled by a theory that predicts a spiral magnetic ground state. The electronic properties of the polar interface between insulating oxides is a subject of great interest 1 , 2 , 3 . An exciting development is the observation of robust magnetism 4 , 5 , 6 , 7 , 8 at the interface of two non-magnetic materials, LaAlO 3 (LAO) and SrTiO 3 (STO). Here we present a microscopic theory for the formation and interaction of local moments that depends on essential features of the LAO/STO interface. We show that correlation-induced moments arise owing to interfacial splitting of orbital degeneracy. We find that conduction electrons with a gate-tunable Rashba spin–orbit coupling mediate ferromagnetic exchange with a twist. We predict that the zero-field ground state is a long-wavelength spiral. Its evolution in an external field accounts semi-quantitatively for torque magnetometry data 5 and describes qualitative aspects of the scanning superconducting quantum interference device measurements 6 . We make several testable predictions for future experiments.